(untitled) (Research, Society and Development, 2021)
Among the more than 1400 species of bats cataloged in the world, only three feed on blood (Hematophagy), these only occur in the Americas (mainly Latin) with wide distribution in Brazil. The feeding activity of vampire bats in humans was described only for Desmodus rotundus, however, in 2016 it was reported for Diphylla ecaudata. Thus, this report describes for the first time the use of human blood under fieldwork conditions by Diaemus youngi. The case occurred in the rural area of the municipality of Ipojuca (08º23’56"S and 35º03’50" W) in the Metropolitan Region of Recife, state of Pernambuco. A 44-year-old resident reported that at dawn on November 1, 2018, he woke up and noticed a bat bleeding his arm, which killed the animal. At dawn, he looked for a health center taking the bat, the patient was referred for appropriate prophylactic measures, receiving serum and vaccine while the bat was sent to LACEN/PE for diagnosis and rabies examination. The specimen was diagnosed based on its morphological characteristics (white spots on the wings, buccal glands, thumb pads, among others) as Deaemus youngi (male; adult). After analysis of direct immunofluorescence and Biological Proof, tested negative for rabies virus. This report highlights the need to deepen ecological studies on the species, mainly related to food items and behavior, as well as on the environmental impacts that may alter the selection of its prey.